The link between communication competence and family communication patterns - Arindra, Fairuza; Wulandari, Maulina Pia; Antoni, Antoni (Jurnal Studi Komunikasi, 2023)
The quality of the close relationship between parents and children is difficult for parents of children with Autism Spectrum Disorder (ASD). Many parents do not have the communication competence to build strong interaction with autistic children, which causes interaction patterns at home to be inappropriate. This study aims to determine the influence of communication competence on the relationship quality of parents and children, determine the effect of family communication patterns on the relationship quality of parents and children, determine the effect of family communication patterns on relational maintenance behaviour, determine the effect of relational maintenance behaviour on relationship quality of parents and children, determine the role of relational maintenance behaviour as a mediator of the influence between communication competence and family communication patterns on the quality of the relationship between parents and children. This study uses quantitative research methods with survey methods and purposive sampling techniques. The results of the sample (N=202) indicate that communication competence significantly affects the quality of the relationship between parents and children, family communication patterns significantly affect the quality of the relationship between parents and children, family communication patterns significantly affect relational maintenance behaviour, and relational maintenance behaviour significantly affects the relationship on the quality of the relationship between parents and children, and relational maintenance significantly mediates the influence between communication competence and family communication patterns on the quality of the relationship between parents and children.